Hard luck - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series), 2013)
After losing his best friend and failing to find an adequate replacement, Greg Heffley decides to rely on the power of luck to turn things around. Without knowledge of how things will turn out, though, Greg wonders if his life will really turn around or if it will continue to spiral out of control.